Consequences of resource competition for sex allocation and discriminative behaviors in a hyperparasitoid wasp - Visser, Bertanne; Le Lann, Cécile; Snaas, Helen; Hardy, Ian C.W.; Harvey, Jeffrey A. (Springer, 2014)
Population-wide mating patterns can select for equal parental investment in both sexes, but limiting resources, such as mates or developmental substrates, can increase competition leading to biased sex ratios in favor of either sex. Such competition for resources typically occurs in spatially structured populations, where dispersal is limited. In this laboratory study, we investigate if and how resource competition affects sex allocation, discriminative behaviors and competitive interactions of the wingless hyperparasitoid Gelis acororum, which exploits patchily distributed hosts. We show that G. acororum sex ratios are male-biased and that this is not a consequence of constrained reproduction by virgin females. Our results suggest that this pattern of reproductive investment, which is only rarely observed in parasitoids, is a consequence of resource limitation, in terms of hosts rather than mates. Further, G. acororum appears not to respond to intrinsic host quality or to prior oviposition in its host. When competing inter-specifically for host resources, G. acororum outcompetes its congener Gelis agilis, but does so mainly when ovipositing on the host first. Overall, our results suggest that host resource limitation could be an important environmental factor shaping sex allocation in G. acororum, with competition taking place both intra- and inter-specifically.